Periodontal Pathogens Among Pre Pubertal, Pubertal And Post Pubertal Girls, In Chennai, India. - KANAKAM ELIZABETH THOMAS,; DR. BALAKRISHNAN D,; DR.MANGAYARKARASI V, (International Journal of Pharma and Bio Sciences, 2015)
The female sex hormones progesterone and oestrogen are seen in increased level during puberty. Some bacteria are able to colonize well at high concentrations of these hormones.In another study microbial change is attributed to a high blood circulation to the gums during Puberty, which leads to gums sensitivity. As a result the gums become tender and show greater irritation to food debris and plaque, leading to gingivitis. Samples were collected from SRM Dental College and SRM Speciality Hospital, Ramapuram Chennai. 30 prepubertal,55 pubertal and 55 post pubertal girls was included for this study. An increase in the percentage of periodontitis was seen from prepubertal to post pubertal stage. Among pre pubertal girls the percentage of periodontitis was 13% where as among pubertal girls it was 52.7%. There was a further increase in post pubertal girls from 52.7% to 61.8%. A comparison of various aerobic and anaerobic bacteria was done among pre pubertal pubertal and post pubertal girls.There is an increase in the percentage of anaerobic bacteria from pre-pubertal stage to the pubertal stage. The highest percentage of anaerobic bacteria that were isolated was Fusobacterium sp., Prevotella sp. and Tannerella forsythia when compared with other anaerobic bacteria. Prevotella sp. Aggregatibacter, Fusobacterium and Tannerella forsythia showed greater prevalence among post pubertal girls. These bacteria are considered as the main pathogens for periodontitis. It can be concluded that there is a notable shift in the oral microflora from pre pubertal to post pubertal stage. Importance of oral hygiene from prepubertal stage will help in maintaining the normal commensal of the mouth. Simultaneously educating parents of girl children can also help in giving their wards a better oral health.